Effect of Temperature Difference on the Steady State Time Using ANSYS (Journal of University of Babylon for Engineering Sciences, 2018)
In this paper, ANSYS-14(APDL) program was used to study the effect of the temperature difference between two faces of samples (∆T) exposed to transient heat transfer on the time required to reach to steady state (S.S.time). Four materials with different thermal properties were chosen.Sample used as a rectangular shape with dimension (1*15) cm. One face of the sample was exposed to three various temperatures (75,125 and 175oC), while the other face was exposed to convection thermal load at 25 °C.  The study showed that the real relationship between the time required to reach the steady state (S.S.time) and the temperature difference between two face of sample is an inverse exponential relationship, which was derived based on the equivalent time. And the result of the relationship between the temperature at the steady state (S.S.Temp.) and (∆T) was a positive linear relationship. While the relationship between (S.S.time) with the thermal diffusivity (α) is an inverse exponential, and the relationship between (S.S.Temp.) and (α) was a positive logarithmic. The results of the study also indicate that the thermal diffusivity (α) effect on (S.S.time) and (S.S.Temp.)  will decreased with approaching the heating source, at the same time the effect of the temperature difference (∆T) on  (S.S.time) and (S.S.Temp.) also decreases with approaching the heating source.